Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region - Alves, Philippe Vieira; de Chambrier, Alain; Luque, José Luis; Scholz, Tomáš (Systematic parasitology, 2017)
As part of a complex revision of proteocephalid cestodes parasitic in freshwater bony fishes of the Neotropical Region, the genus Chambriella Rego, Chubb & Pavanelli, 1999 is redefined based on detailed examination of type-specimens and newly collected material of both nominal species of the genus. This examination revealed that the type-species C. agostinhoi (Pavanelli & Santos, 1992) from Zungaro jahu (Ihering) (type-host) and Z. zungaro (Humboldt) is indistinguishable from Lenhataenia megacephala (Woodland, 1934) from Sorubimichthys planiceps (Spix & Agassiz) (all hosts Siluriformes: Pimelodidae), the type- and only species of the genus. New molecular data (partial sequences of the large subunit nuclear ribosomal RNA gene) support the conspecificity of these taxa. As a result, Lenhataenia de Chambrier & Scholz, 2008 becomes a junior synonym of Chambriella and its type-species, C. agostinhoi, a junior synonym of C. megacephala (Woodland, 1934) n. comb. The second species of Chambriella, C. paranaensis (Pavanelli & Rego, 1989) from Hemisorubim platyrhynchos (Valenciennes), is transferred to a new genus, Riggenbachiella n. g., as R. paranaense (Pavanelli & Rego, 1989) n. comb. Riggenbachiella amazonense n. sp. (syn. Chambriella sp. of de Chambrier & Scholz, 2008) from S. planiceps (type-host), Phractocephalus hemioliopterus (Bloch & Schneider) and Z. zungaro is described and designated as the type-species of the new genus. Riggenbachiella n. g. is placed in the subfamily Monticelliinae Mola, 1929, because of the cortical position of the testes, ovary, vitelline follicles and uterus, and is mainly characterised by the possession of a sigmoid cirrus-sac with voluminous, chambered internal seminal vesicle, and bi-loculate suckers.
Keywords: Cestoda; Animals; Brazil; druhová specificita; zvířata; Catfishes; DNA, Helminth; DNA helmintů; řeky; Brazílie; Intestines; Rivers; sumci; Species Specificity; střeva